New insights into interspecies relationships, chromosomal evolution, and hybrid identification in the Lycoris Herb. - Yue Zhang; Shujun Zhou; Yu Chen; Pengchong Zhang; Yongchun Zhang; Junhuo Cai; Zixuan Nie; Lu Zhang (BMC Plant Biology)
Abstract Background Frequent interspecific hybridization, unclear genetic backgrounds, and ambiguous evolutionary relationships within the genus Lycoris pose significant challenges to the identification and classification of hybrids, thereby impacting the application and development of Lycoris. This study utilizes karyotype structure, genome size, and fluorescent in situ hybridization (FISH) technology to explore the chromosomal evolution and hybrid identification of Lycoris employing three approaches at the cytogenetic level. Results The findings indicate that species with a smaller basic chromosome number exhibit less asymmetry than those with a larger basic chromosome number, suggesting that species with different basic chromosome numbers may have followed different evolutionary pathways. Lycoris aurea has a more symmetrical karyotype, which may be the plesiomorphic state, reflecting an evolutionary transition from symmetry to asymmetry in Lycoris chromosomes. Systematic clustering of 18 Lycoris species is consistent with chromosomal karyotype classification, primarily dividing into two groups: species with M + T + A type an M + T type as one group, and A type as another group. The average nuclear genome size (C-value) of the Lycoris genus is 22.99 Gb, with the smallest genome being that of L. wulingensis (17.10 Gb) and the largest being L. squamigera (33.06 Gb). Chromosome length is positively correlated with the C-value, and the haploid genome size (Cx-value) decreases with an increase in basic chromosome number (x). The FISH technique can quickly identify and authenticate artificial hybrids, thus inferring the parentage of natural hybrids. Conclusion The study reveals the genetic background and interspecific relationships of 18 Lycoris species, identifies the authenticity of artificial Lycoris hybrids, and infers the possible parentage of natural hybrids, offering technical insights for the identification, classification, and genomic projects of Lycoris.